Two mitochondrial DNA polymorphisms modulate cardiolipin binding and lead to synthetic lethality - Chiang, Ason C Y; Ježek, Jan; Mu, Peiqiang; Di, Ying; Klucnika, Anna; Jabůrek, Martin; Ježek, Petr; Ma, Hansong (Nature communications, 2024)
Genetic screens have been used extensively to probe interactions between nuclear genes and their impact on phenotypes. Probing interactions between mitochondrial genes and their phenotypic outcome, however, has not been possible due to a lack of tools to map the responsible polymorphisms. Here, using a toolkit we previously established in Drosophila, we isolate over 300 recombinant mitochondrial genomes and map a naturally occurring polymorphism at the cytochrome c oxidase III residue 109 (CoIII109) that fully rescues the lethality and other defects associated with a point mutation in cytochrome c oxidase I (CoIT300I). Through lipidomics profiling, biochemical assays and phenotypic analyses, we show that the CoIII109 polymorphism modulates cardiolipin binding to prevent complex IV instability caused by the CoIT300I mutation. This study demonstrates the feasibility of genetic interaction screens in animal mitochondrial DNA. It unwraps the complex intra-genomic interplays underlying disorders linked to mitochondrial DNA and how they influence disease expression.
Keywords: Mitochondria; Drosophila; DNA, Mitochondrial; umělé letální mutace; kardiolipiny; Electron Transport Complex IV; Animals; Cardiolipins; Synthetic Lethal Mutations; respirační komplex IV; mitochondrie; zvířata; mitochondriální DNA